1989
DOI: 10.1530/jrf.0.0850471
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the release of ovine trophoblast protein-1 by the conceptus and the production of polypeptides by the maternal endometrium of ewes

Abstract: We studied the biosynthesis of two proteins, p70 (Mr 70,000; pI 4.0) and p15 (Mr 15,000; pI 5.7), by endometrial tissues from ewes between Days 12 and 24 of pregnancy and between Days 12 and 16 of the oestrous cycle to determine whether production of the two was correlated with the period of biosynthesis of ovine trophoblast protein-1 (oTP-1) by the conceptus. We also compared the protein synthetic activities of endometrium from gravid and non-gravid horns of pregnant ewes at Days 14, 16 and 18 in which the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…[1,2]. Bovine trophoblast protein-1 (bTP-1) is a small (22)(23)(24)(25)(26), acidic (pI = 5.7-6.5) polypeptide that is the major polypeptide shown to be synthesized and secreted in vitro by the bovine conceptus during the critical time of maternal recognition of pregnancy (Days [17][18][19][20] [3,4]. Attachment of the bovine conceptus to the uterine endometrium occurs between Days 18 and 24 of gestation [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2]. Bovine trophoblast protein-1 (bTP-1) is a small (22)(23)(24)(25)(26), acidic (pI = 5.7-6.5) polypeptide that is the major polypeptide shown to be synthesized and secreted in vitro by the bovine conceptus during the critical time of maternal recognition of pregnancy (Days [17][18][19][20] [3,4]. Attachment of the bovine conceptus to the uterine endometrium occurs between Days 18 and 24 of gestation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the actions of IFNs are local, since the receptors for oTP-1 are present in ovine endometrium [16,17] and can be competitively displaced by recombinant bovine IFN-at (rbIFN-a) [18]. Several studies have revealed that oTP-1 can also selectively inhibit or stimulate the synthesis of various endometrial polypeptides in sheep [19,20] that can be mimicked by IFN-a [21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the current study, the potential existed for IFNs to inhibit secretion of radiolabeled proteins and thereby provide the appearance of enhanced secretion of the remaining protein. Our group [7] and others [22,23] have reported that total secretion of endometrial proteins is not affected by IFN-T treatment or by pregnancy status. This was determined by examining the incorporation of L-[ 3 H]leucine into secreted protein (i.e., specific activity; cpm/pg).…”
Section: Discussionmentioning
confidence: 63%
“…Endometrial explants were cultured in serum-free medium under conditions used by our group [7,8] and others [22][23][24]. Endometrium was collected from cows (n = 5) on Day 18 of pregnancy and cultured in leucine-deficient medium, in the absence or presence of 25 nM rbIFN-T. Cultures were maintained in an atmosphere of 50% 02:45% N 2 :5% CO 2 at 37°C to characterize timing of secretion of the uterine proteins.…”
Section: Timing Of Secretion Of Endometrial Proteinsmentioning
confidence: 99%
“…The unilateral pregnant sheep model (Moor and Rowson, 1966) enables changes in the expression of endometrial genes in the presence of conceptuses to be studied during early pregnancy (Sharif et al, 1989;Sandra et al, 2005). In sheep, cellular contact between conceptus trophectoderm and epithelium of the caruncular areas occurs on day 16 of post-mating, a dynamic process completed by day 22 of pregnancy (Spencer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%